The Cultural Beliefs, Values, Social Support and Health Perspectives of Black Women and Men: Postpartum Depression and Anxiety - Stampp, Tashi (Université d'Ottawa / University of Ottawa, 2025)
Background: Research on postpartum anxiety and postpartum depression often adopts a gender-exclusive, binary framework, focusing on women and overlooking diverse racial and cultural perspectives. A decade of studies on men's experiences with postpartum anxiety and depression centers on white men, while research on Black men's postpartum mental health remains scarce. Similarly, despite well-documented inequities in care, Black mothers face a higher risk of developing postpartum depression compared to other racial groups, highlighting the need to address these disparities and the unique racial, cultural, and social factors affecting their mental health. Objective: This qualitative study addresses these gaps by exploring the cultural beliefs, values, health perspectives, and perceived social support related to postpartum anxiety and depression among Black men and women. Methods: 33 qualitative, semi-structured interviews were conducted virtually. Participants were eligible if they self-identified as men or women, were Black parents with rights to one child and were present at their child's birth in Canada within 2019 - 2025. Participants were recruited via reverse snowball sampling. Interviews were coded inductively for relevant patterns. Data analysis was guided by Critical Race Theory and Black Feminist Theory, displaying the interplay of race, culture, and gender in postpartum. Results: The themes for men (n=20) were: (1) the quiet struggle of fatherhood; (2) the weight of strength; (3) inclusive care for fathers; (4) balancing support and self-care, and (5) cultural perspectives on mental health. The themes for women (n=13) were: (1) a healing love: support and spirituality; (2) barriers to mental health care; (3) beyond the baby blues; (4) cultural tensions in postpartum health, and (5) relational shifts: before and after birth. Conclusion: These findings highlight the need for culturally tailored resources to support Black parents, offering a foundation for future research and interventions to enhance equitable postpartum mental health support. -- Contexte : La recherche sur l'anxiété du post-partum et la dépression du post-partum adopte souvent un cadre binaire et exclusif de genre, se concentrant sur les femmes et négligeant les diverses perspectives raciales et culturelles. Une décennie d'études sur les expériences des hommes en matière d'anxiété et de dépression post-partum se concentre sur les hommes blancs, tandis que les recherches sur la santé mentale post-partum des hommes noirs restent rares. De même, malgré des inégalités bien documentées en matière de soins, les mères noires courent un risque plus élevé de développer une dépression du post-partum que les autres groupes raciaux, ce qui souligne la nécessité de s'attaquer à ces disparités et aux facteurs raciaux, culturels et sociaux uniques qui affectent leur santé mentale. Objectif : Cette étude qualitative vise à combler ces lacunes en explorant les croyances culturelles, les valeurs, les perspectives en matière de santé et le soutien social perçu en rapport avec l'anxiété du post-partum et la dépression du post-partum chez les hommes et les femmes de race noire. Méthodes : 33 entretiens qualitatifs semi-structurés ont été menés virtuellement. Les participants étaient éligibles s'ils s'identifiaient comme des hommes ou des femmes, étaient des parents noirs ayant des droits sur un enfant et étaient présents à la naissance de leur enfant au Canada entre 2019 et 2025. Les participants ont été recrutés par échantillonnage en boule de neige inversée. Les entretiens ont été codés de manière inductive afin d'y déceler des schémas pertinents. L'analyse des données a été guidée par la théorie critique de la race et la théorie féministe noire, montrant l'interaction de la race, de la culture et du genre dans le post-partum. Résultats : Les thèmes abordés par les hommes (n=20) étaient les suivants : (1) la lutte silencieuse de la paternité ; (2) le poids de la force ; (3) les soins inclusifs pour les pères ; (4) l'équilibre entre le soutien et les soins personnels, et (5) les perspectives culturelles sur la santé mentale. Les thèmes abordés par les femmes (n=13) sont les suivants : (1) un amour qui guérit : soutien et spiritualité ; (2) les obstacles aux soins de santé mentale ; (3) au-delà du baby blues ; (4) les tensions culturelles dans la santé post-partum, et (5) les changements relationnels : avant et après la naissance. Conclusion : Ces résultats soulignent le besoin de ressources culturellement adaptées pour soutenir les parents noirs, offrant une base pour la recherche et les interventions futures afin d'améliorer le soutien équitable à la santé mentale post-partum.
Keywords: Postpartum depression; Postpartum anxiety; Black women; Black men; Thematic analysis; Qualitative research